2022
DOI: 10.13005/bpj/2546
|View full text |Cite
|
Sign up to set email alerts
|

Biofilm Formation and its Association with Gram Negative Sepsis Pathogenicity

Abstract: Background and objectives: Biofilm formation is an important virulence factor that protects an organism from antimicrobial agents as well as host immune effectors, thus allowing organisms to invade, survive, and cause persistent-reoccurring infection in host cells. The aim of this study was to investigate the ability of sepsis-causing gram-negative bacteria to form biofilms, evaluate the association between antibiotic resistance pattern and biofilm formation, determine the role and influence of biofilm formati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…However, the presence of association between antibiotic resistance and biofilm formation capacity is still debated by some researchers. 40,41 This study showed that ecpA, fimA, mrkD, and mrkA genes were harbored by all biofilm producing K. pneumoniae strains, whereas fimH was determined in 93% (82/88) of isolates. The prevalence of mrkA, ecpA, and fimH (100%) in our study were almost similar to that reported by Alcántar-Curiel et al 21 In addition, consistent with our results, Alcántar-Curiel et al, 21 showed that 80% of K. pneumoniae isolates were able to produce biofilm and all isolates carried the mrkA gene.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…However, the presence of association between antibiotic resistance and biofilm formation capacity is still debated by some researchers. 40,41 This study showed that ecpA, fimA, mrkD, and mrkA genes were harbored by all biofilm producing K. pneumoniae strains, whereas fimH was determined in 93% (82/88) of isolates. The prevalence of mrkA, ecpA, and fimH (100%) in our study were almost similar to that reported by Alcántar-Curiel et al 21 In addition, consistent with our results, Alcántar-Curiel et al, 21 showed that 80% of K. pneumoniae isolates were able to produce biofilm and all isolates carried the mrkA gene.…”
Section: Discussionmentioning
confidence: 83%
“…In line with our results, Vuotto et al 39 showed a positive relationship between antibiotic resistance profile and biofilm‐forming ability in XDR K. pneumoniae strains. However, the presence of association between antibiotic resistance and biofilm formation capacity is still debated by some researchers 40,41 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bio lms are microbial-derived surface-associated cells that are enclosed in an extracellular polymeric substance matrix and attached to substratum or to each other in an irreversible way. Bio lms are important virulence factors which are produced through a serial process beginning with a single species of bacteria with mbria, pili or agella attaching to the conditioning lm then progressing to form microcolonies and colonies after longer exposure eventually forms a mass that detaches after maturation 3 . Bacteria form bio lm as a part of their survival mechanisms [4].…”
Section: Introductionmentioning
confidence: 99%
“…Bacteria form bio lm as a part of their survival mechanisms [4]. Bio lm formation is a serious clinical issue because bio lms promotes antimicrobial resistance by slowing down antimicrobial diffusion and also by facilitating plasmid exchange [3].Bio lm formation is also associated with the severity, persistence and relapse of infection [3] For Enterobacterales resistance to the beta lactam class of antibiotics is particularly concerning because they are the cornerstone of treatment for these infections. Resistance to beta lactam antibiotics can occur via e ux pumps, altered penicillin binding sites and beta lactamases which cleave the beta lactam ring and inactivate the target antibiotic [2] The present study will be conducted to nd out the bacteria belonging to Enterobacterales family causing septicaemia in our community and their ability to form bio lms and also to correlate the antimicrobial resistance pattern of the organisms with bio lm forming capacity.…”
Section: Introductionmentioning
confidence: 99%